The use of dietary supplements for mental health among the Saudi population: A cross-sectional survey - Deemah Alateeq; Maha A. Alsubaie; Faridah A. Alsafi; Sultanah Hisham Alsulaiman; Ghazwa B. Korayem (Elsevier, 2022)
Introduction: Despite limited evidence about the efficacy and safety of dietary supplements (DSs) for improving mental health, people with or without mental disorders often tend to use them, especially during the ongoing COVID-19 pandemic. Previous studies focused on DS use for maintaining or improving overall health; Therefore, this study aimed to assess the prevalence of DSs for mental health among the SA population and to determine the factors that affect their use. Methods: This cross-sectional study was based on an online survey of Saudi Arabian participants between July and August 2021 with an anonymous, self-completed questionnaire distributed using convenience sampling. The questionnaire included queries related to demographic information, DS use assessment, and mental health evaluation using the Patient Health Questionnaire (PHQ-9), the Generalized Anxiety Disorder 7-item (GAD-7), questionnaire, and the Insomnia Severity Index (ISI). Results: In total, 443 participants from various regions of Saudi Arabia completed the questionnaire. The prevalence of DS use in the Saudi population was 44%. Vitamin D (28%) and melatonin (20%) were the most commonly reported DSs used for mental health. The odds of DS use were three times higher in responders with previous mental health diagnoses (OR: 2.972; 95% CI: 1.602-5.515). Furthermore, the chances of using DSs almost doubled in patients with sub-threshold and moderate to severe insomnia (OR: 1.930; 95% CI: 1.191-3.126 and OR: 2.485; 95% CI: 1.247-4.954, respectively). Conclusion: Responders diagnosed by a specialist with psychiatric disorders or current insomnia had a higher chance of using DSs. Thus, healthcare providers must provide evidence-based information regarding DSs for mental health improvement and encourage the public to consult healthcare professionals before self-medicating for mental health problems.